The willingness and actual behaviour of teachers’ participation in university governance in China based on theory of planed behaviour - Wang, Wenjing (Penerbit UMP, 2024)
The modernisation of education governance systems and capacities is an integral part of national governance reform. Despite the growing importance of university governance, research on teachers’ participation in this domain remains limited. Grounding in the Theory of Planned Behaviour (TPB) and focusing on Chinese universities teachers, the research investigates the impact of attitudes, subjective norms and perceived behavioural control on teachers’ willingness to engage in university governance, aims to perform and propose a conceptual model of teacher development policy. Data will be collected through a survey questionnaire from diverse teachers in Hebei Province. The study will include demographic information, attitudes, subjective norms, perceived behavioural control, willingness and actual participation in university governance. The sample size will be no fewer than 400 teachers selected through cluster sampling. Data analysis will involve descriptive analysis, correlation analysis, regression analysis, mediation effect analysis, structural equation modeling (SEM) analysis and effect size analysis. The significance of this research lies in its implications on various stakeholders. For the government, it contributes to national governance modernisation by encouraging teachers’ active participation. For universities, it helps administrators understand teachers’ needs and develop tailored governance strategies. Teachers gain a clearer understanding of their roles in governance, and administrators can optimise governance mechanisms and enhance teachers’ capacity and willingness to participate. Furthermore, the findings foster a positive campus governance atmosphere, benefiting students. In summary, this study provides valuable insights into teachers’ participation in university governance, optimising governance mechanisms and promoting the modernisation of university governance systems and capacities.